IMPROVING THE STUDENTS SPEAKING ABILITY BY USING THEMATIC MATERIALS (A CLASSROOM ACTION RESEARCH TO THE FIRST YEAR STUDENTS OF MTsN. MODEL MAKASSAR) - Siti Yudiarti Fajriah Rusdi (Universitas Islam Negeri Alauddin Makassar, 2015)
The objective of this study was to improve the speaking ability of the students at the first grade of MTsN. Model Makassar. The method of this research was Classroom Action Research (CAR) that is conducted to the first grade students of MTsN. Model Makassar in academic year 2014/2015. The subject of the research consists of twenty five students; there are twelve boys and thirteen girls. The instruments are spoken test and observation guidelines. The research design applied in this study was a collaborative classroom action research consisting of 2 cycles covering 3 meetings for each cycle. The findings of this study showed improvement of the students’ speaking ability from the first to the second cycle have improve highly. Where the mean score ofvocabulary terms was 2 for the pre-cycle test become 3.28 for the second cycle post-test. Besides that, the mean score of grammar in the pre-cycle test wa 1.84 increase 3.08 in the second cycle post-test. Same as the pronunciation term, the students score from pre-cycle test to the second cycle test came up from 1.96 to 3.04. Furthermore for the students speaking accuracy and fluency, their score also increase from 1.44 became 2.92. This research was successful to improve the students speaking ability by using thematic materials.